On Open Questions in Holocaust Education - Danilo D. Kovač (University of Belgrade, Teacher Education Faculty, 2021)
Even though recent decades have borne witness to an increased educational interest in teaching the Holocaust, academic stances on why the topic should be taught still vary significantly. The aim of this paper is to present teaching interventions that would help educators to navigate through one of the most important open questions in Holocaust education: the question of aims. Three Holocaust-related teaching interventions, which themselves use open questions as the basis for teaching and learning, are presented and analysed. The open questions, as the background, allow the educators to simultaneously shift between various teaching aims. The interventions addressing the question of heroes, victims and bystanders, causal analysis of the Holocaust, and the responsibility of the Allies for the escalation of the Holocaust, are arranged in such a way so as to lead students from their day-to-day knowledge, through historical concepts, finally ending up addressing more abstract concepts. The analysis draws on literature related to both Holocaust education and the teaching of controversial issues, and covers a range of topics; from practical to more philosophical